Understanding ESL practitioners’ challenges in teaching academic english for technical and engineering purposes - Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Supyan, Hussin; Nor Fariza, Mohd Nor (2017)
The English for Specific Academic Purposes (ESAP) competencies of ESL practitioners teaching at Malaysian engineering and technical (MTUN) universities is vital in ensuring quality learning and teaching of language and communication skills at the institutions. In understanding the necessity of the competencies, this study aims to explore the challenges faced by the practitioners teaching the skills. The study comprised data gathered from a survey on the practitioners and semi structured interviews of the experts in technical and engineering fields. Findings from both quantitative and qualitative inquiries on the practitioners and experts revealed several challenges; therefore, the necessity of wider knowledge and understanding of ESAP in teaching the context became the prevalent competency for the practitioners in overcoming the challenges. The practitioners’ competency was substantially indispensable because it could affect their learners’ interest in learning the skills as well as in understanding the content subject. The challenges faced by the practitioners call for a specific professional development training to elevate their status and recognition. Subsequently, it implicates the need for the institutions and local quality agencies to review and specify the requirement and guideline for ESL practitioners teaching the skills in a specific academic technical and engineering context.